Potential Role of Lycopene in the Treatment of Hepatitis C and Prevention of Hepatocellular Carcinoma - Seren, Soley; Mutchnick, Milton; Hutchinson, Daryl; Harmanci, Ozgur; Bayraktar, Yusuf; Mutchnick, Sean; Kucuk, Omer (Routledge Journals, Taylor & Francis Ltd, 2008)
Hepatitis C virus (HCV) infection and hepatocellular carcinoma (HCC) are growing health problems around the world. Oxidative stress plays a significant role in the initiation and progression of hepatocellular damage and possibly in the development of HCC in HCV infected patients. In vitro, animal and clinical studies suggest that lycopene, a nonprovitamin A carotenoid and a potent antioxidant, may attenuate the liver injury and possibly prevent the development of HCC. In this article, we discuss the relationship between HCV infection and oxidative stress and review the potential role of lycopene in the treatment of HCV and prevention of HCC.
Keywords: Liver Preneoplastic Foci; Chronic Viral-Hepatitis; Virus-Infection; Vitamin-E; Serum Aminotransferase; Oxidative Stress; Alpha-Tocopherol; Beta-Carotene; United-States; Core Protein